2012
DOI: 10.1002/bdra.23049
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal age and birth defects of unknown etiology ― United States, 1997–2007

Abstract: BACKGROUND-Birth defects affect 3% of babies born, and are one of the leading causes of infant mortality. Both younger and older maternal age may pose increased risks for certain birth defects. This study assessed the relationship between maternal age at the estimated delivery date and the risk for birth defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
82
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 55 publications
8
82
2
Order By: Relevance
“…This result was in accordance with many other studies 1315,37,4042. According to Gill et al,17 increased risks for several cardiac defects, including ventricular septal defects, atrial septal defects, and Tetralogy of Fallot, were observed for mothers who were 40+ years of age. In the present study, a U-shaped maternal age effect on congenital malformations of the aortic and mitral valves was observed.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This result was in accordance with many other studies 1315,37,4042. According to Gill et al,17 increased risks for several cardiac defects, including ventricular septal defects, atrial septal defects, and Tetralogy of Fallot, were observed for mothers who were 40+ years of age. In the present study, a U-shaped maternal age effect on congenital malformations of the aortic and mitral valves was observed.…”
Section: Discussionsupporting
confidence: 91%
“…They found that all birth defects combined and all nonchromosomal birth defects showed increased odds ratios for young and advanced maternal age, with a more pronounced increase for the group that included chromosomal defects. Overall, the relationship between maternal age and the prevalence of birth defects per birth or per live birth was similar in many previous studies in that these studies showed U-curves or gradual J-curves for nonchromosomal birth defects and extreme J-curves for chromosomal abnormalities 1117. The present results also support previous findings that the effect of advanced maternal age, especially over 40, on nonchromosomal birth defects was not large compared to the effect on chromosomal abnormalities.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Data from the National Birth Defects Prevention Study (NBDPS), which includes the states of Arkansas, California, Georgia, Iowa, Massachusetts, New Jersey, New York, North Carolina, Texas, and Utah, revealed that mothers ≥35 years were 2.1 times more likely to have a newborn with hypospadias than women <25 years of age (OR: 2.1, 95% CI: 1.5-2.8) between the years of 1997 to 2000 [11]. Another study that employed the NBDPS database, a positive association was found for advanced maternal age (> 40 years) and hypospadias between the years of 1997 to 2007 (OR: 2.0, 95% CI: 1.4-3.0) [12]. In Puerto Rico, data from the Birth Defects Prevention and Surveillance System of the Department of Health of Puerto Rico (2007 – 10) revealed an OR of 2.77 (95% CI: 1.26-6.13) for > 40 years old mothers [13].…”
Section: Discussionmentioning
confidence: 99%